Nilai-Nilai Karakter dalam Kurikulum Humanistik di FITK IAIN Surakarta - Maslamah Maslamah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
This research was conducted to find the values of the character in curriculum based Humanistic. Humanistic curriculum is a model curriculum with emphasis on student-centered learning. By way of this curriculum, educationcan return to its original role and function, which is to increase human dignity and. The catagory ofthis research is leterary and took place in FITK (Faculty of Education), IAIN (State Islamic Institut). The data of research were handouts and reference books that used by lecturers of humanistic-based subjects. The results of this research are: 1) the majority of the subject materials based on humanistic in FITK contains muchcharacter values, such as: love peace, tolerance, empathy, solidarity, asceticism, sincere and so on; 3) in addition, character values are also internalized through a learning process; 3) The values of character that nothing comes from the teachings of Islam, philosophy and civilization of community.Keywords: Character Values, Humanistic Curriculum.